Lesions of hypertrophic osteopathy in the forelimbs of a dog associated with pulmonary metastasis from a periosteal osteosarcoma - Pachamé, Andrea V.; Beltrán, Marcos J.; Recchiuti, Nestor E.; Portiansky, Enrique L.; Massone, Adriana R.; Gimeno, Eduardo J. (Brazilian Journal of Veterinary Pathology, 2017)
Hypertrophic osteopathy is commonly associated with primary lung neoplasms. It may also be secondary to intrathoracic lesions such as pulmonary metastasis, granulomatous pleurisy and chronic pneumonia, among others. It is characterized by progressive proliferation of sub periosteal bone tissue in limb bones. Clinically, patient usually exhibits lameness. It is a rare disease most frequently observed in dogs among domestic animals. A case of a dog with pulmonary hypertrophic osteopathy associated with pulmonary metastases coming from an appendicular periosteal osteosarcoma is reported.